Efektivitas Dakwah Amaliyah Thariqat Qodiriyah Naqsyabandiyah Suryalaya dalam Pembinaan Akhlak Santri di Pondok Pesantren Jagat Arsy - Ridwan Nurarifin Ridwan; Rodliyah Khuza'i; Hendi Suhendi (UNISBA Press, 2023)
Abstract. Tariqat is a way or way for someone to get closer to Allah with the aim of getting to Allah. Before someone carries out the amaliyah of the order, he must carry out talqin, then carry out the deeds that are in the order. Amaliyah in the Tariqat Qadiriyyah Naqsyabandiyyah Suryalaya, namely dhikr, khataman, manaqib and riyadhah whose purpose is to forgive oneself, especially in the moral aspects of karimah, tazkiyatun nafs, taqarub, muraqabbah, mahabbah and ma'rifat. The research method used is a